Виборча інженерія як законодавче проектування - Афанасьева, Марьяна Владимировна; Афанасьєва, Мар'яна Володимирівна; Afanas'eva, М. (My University, 2010)
The lack of a scientiﬁ c approach to the term "electoral engineering" actualizes the theoretical research in this area. In the constitutional law science "electoral engineering" is deficiently research phenomenon, as evidenced by the lack of monographic works. The term is used in two ways: as introduction in practice electoral technologies of organization electoral campaigns and as a legislative planning of participants's rules of conduct of electoral process.
Афанасьєва М. В. Виборча інженерія як законодавче проектування / М. В. Афанасьєва // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 63-68.
Keywords: виборча інженерія; законодавче проектування; вибори; виборче законодавство; удосконалення виборчого законодавства; избирательная инженерия; выборы; избирательное законодательство; усовершенствование избирательного законодательства; Election Engineering; законодательное проектирование; legislative design; improvement of the electoral legislation; electoral law; elections